2008
DOI: 10.1002/ajmg.a.32216
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐mapping subtelomeric deletions and duplications by comparative genomic hybridization in 42 individuals

Abstract: Human subtelomere regions contain numerous gene-rich segments and are susceptible to germline rearrangements. The availability of diagnostic test kits to detect subtelomeric rearrangements has resulted in the diagnosis of numerous abnormalities with clinical implications including congenital heart abnormalities and mental retardation. Several of these have been described as clinically recognizable syndromes (e.g., deletion of 1p, 3p, 5q, 6p, 9q, and 22q). Given this, fine-mapping of subtelomeric breakpoints is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
2
31
1
Order By: Relevance
“…TEL array provides complete ($1.5Â coverage) tiling path coverage for the terminal 5 Mb region of 6p25 [DeScipio et al, 2007]. The TEL array data revealed a conflict with our previously reported mapping data for Patient 8, revealing an $3.9 Mb deletion (defined by BAC RP11-590A14) rather than $3.0 Mb as we had previously reported [DeScipio et al, 2005].…”
Section: Cytogenetics and Molecular Geneticscontrasting
confidence: 71%
See 2 more Smart Citations
“…TEL array provides complete ($1.5Â coverage) tiling path coverage for the terminal 5 Mb region of 6p25 [DeScipio et al, 2007]. The TEL array data revealed a conflict with our previously reported mapping data for Patient 8, revealing an $3.9 Mb deletion (defined by BAC RP11-590A14) rather than $3.0 Mb as we had previously reported [DeScipio et al, 2005].…”
Section: Cytogenetics and Molecular Geneticscontrasting
confidence: 71%
“…The minimally deleted critical region in 6p subtelomere deletion syndrome, as defined by this individual, was therefore determined to be the terminal $1.3 Mb region of chromosome 6p [DeScipio et al, 2005]. We have subsequently reanalyzed the 6p-deleted region in Patient 8 by array CGH using a custom made BAC and cosmid based DNA array (TEL array) with high-resolution coverage of telomeric and subtelomeric regions [DeScipio et al, 2007].…”
Section: Cytogenetics and Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the preferential involvement of certain chromosomes in structural anomalies could be researched in their genomic architecture. Indeed, segmental duplications, representing 4-5% of the human genome (Bailey et al, 2002;Zhang et al, 2005), have been found to be predisposing factors in chromosomal rearrangements leading to disease (Stankiewicz et al, 2002) and, more recently, recurrent subtelomeric BKPs have been localized to genomic regions containing low copy repeats (DeScipio et al, 2008). The extent of segmental duplications has been reported to vary from 1 to 14% among the 24 chromosomes, with an approximate average of 4% (Zhang et al, 2005).…”
Section: Chromosome Recurrence and Breakpoints Distributionmentioning
confidence: 99%
“…The many patients described to date had terminal 6p25 deletions [Law et al, 1998;Nishimura et al, 1998;Gould et al, 2004;Le Caignec et al, 2005;Rosenberg et al, 2006;Martinez-Glez et al, 2007;DeScipio et al, 2008;Martinet et al, 2008], interstitial 6p25 deletions [van Swaay et al, 1988;Davies et al, 1999;Lehmann et al, 2002;Koolen et al, 2005;Chanda et al, 2008;D'Haene et al, 2011], or mixed 6p25 deletions [Bedoyan et al, 2011]. However, molecular characterization of the deletion was performed in only a minority of patients (using FISH and/or STS marker analysis in 26 cases and array-CGH or SNP chips in 18 cases).…”
Section: Introductionmentioning
confidence: 95%